2019
DOI: 10.1063/1.5113850
|View full text |Cite
|
Sign up to set email alerts
|

Efficient chemical vapour deposition and arc discharge system for production of carbon nano-tubes on a gram scale

Abstract: Three indigenous systems—the underwater arc discharge setup, the inert environment arc discharge system, and the chemical vapor deposition (CVD) system—for the gram-scale production of carbon nanotubes were designed and fabricated. In this study, a detailed description of the development and fabrication of these systems is given. Carbon nanotubes were synthesized by using all the three systems, and comparative analyses of the morphology, composition, and purity were done. The synthesized materials were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…Previous studies employing camphor in combination with ferrocene as precursors for CVD also yielded densely packed CNT films with a similar appearance as observed for our growth parameters. Moreover, comparable diameters between 20 and 60 nm were reported for multi-wall carbon nanotubes [24,25,36]. Thus, we assume that multi-wall CNTs were produced in this study based on the observed tube diameters.…”
Section: Cnt Morphologysupporting
confidence: 78%
“…Previous studies employing camphor in combination with ferrocene as precursors for CVD also yielded densely packed CNT films with a similar appearance as observed for our growth parameters. Moreover, comparable diameters between 20 and 60 nm were reported for multi-wall carbon nanotubes [24,25,36]. Thus, we assume that multi-wall CNTs were produced in this study based on the observed tube diameters.…”
Section: Cnt Morphologysupporting
confidence: 78%
“…35 Cost: 40$ per g Chemical reduction: chemical reduction in GO sheets with sodium borohydride led to the formation of rGO. 34 Cost: Low-cost, high-yield protocol Laser ablation: laser source, furnace, inert atmosphere, metal catalyst-graphite composite. 35 Cost: due to high capital cost of the laser and the fewer quantity of CNT aer nal purication, this method is not commercially viable Floating catalyst method: tubular reactor, quartz tube, thermocouples, inert gas.…”
Section: Cnt Go Rgomentioning
confidence: 99%